Tinjauan Yuridis Sengketa Tanah Adat di Marfenfen. Studi Kasus No. Putusan 7/Pdt.G/2021/Pn.Dobo - Zulkarnain, Fahmi; Arifin, Zaenal (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2025)
Customary law communities are recognized as one of the legal subjects of the state under statutory regulations. These communities have a multidimensional relationship with customary land (ulayat), not only as an economic resource but also as an inseparable part of their socio-cultural life. This study aims to examine and analyze the settlement of customary land disputes in the Marfenfen area, which was occupied by the Indonesian Navy (TNI AL), using Case Decision Number 7/Pdt.G/2021/PN.Dobo as the focal point. The research method employed is normative juridical (doctrinal) research by reviewing the applicable statutory provisions as the basis for problem analysis. The findings indicate that land, as a fundamental human need, often becomes the object of disputes due to its vital value and limited availability. Customary land disputes demand proper handling by the competent authorities through various mechanisms. So far, dispute resolution has been carried out through litigation in the courts; however, over time, deliberation and consensus have increasingly been chosen as more suitable methods, as they better accommodate the interests of the parties involved. Disputes rooted in interests and needs tend to be more easily resolved through deliberation, provided both parties are open and willing to seek the best solution for all.